Teacher Creativity in Aqidah Akhlak Learning After the Covid-19 Pandemic at Madrasah Ibtidaiyah: Kreativitas Guru Dalam Pembelajaran Aqidah Akhlak Pasca Pandemi Covid – 19 di Madrasah Ibtidaiyah - Trisnawati, Cici Cindy Indah; Salahuddin, Rahmad (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the creativity of teachers in learning moral aqidah after the Covid-19 pandemic at MI Ma'arif Pamotan. This research is a descriptive qualitative research. In this study, the informants were mi principal Ma'arif Pamotan, moral aqidah teachers and female students. The location of this study was conducted at MI Ma'arif Pamotan. Data collection techniques in the form of interviews, observations, documentation. Data analysis and interpretation techniques use analysis models from Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results of this study show that the teacher's creativity in learning aqidah akhlak consists of a form of teacher creativity which is manifested in the management of kela, learning methods in the form of Problem Based Learning, jigsaw-type cooperative methods and the resulting work, namely props in the form of sholih children's trees and intelligent puppets.